Resident as Preceptor: An Ambulatory Internal Medicine Curriculum for Third-Year Resident Precepting - Rachel Hilburg; Andrew Coyle (Association of American Medical Colleges, 2020)
Introduction The role of outpatient preceptor is a core component of many careers within internal medicine (both general internal medicine and subspecialty practice), yet opportunities to learn and practice this skill during residency training are limited. The purpose of this initiative was to introduce outpatient clinic precepting into the third-year ambulatory experience with a didactic and experiential curriculum. Methods Internal medicine third-year residents received a 1-hour didactic on outpatient precepting and participated in a precepting session in their ambulatory block rotation during the 2017-2018 academic year. During this session, third-year residents precepted their first- and second-year colleagues in the residency clinic with faculty supervision. Residents were surveyed before the didactic and after the precepting experience to assess precepting comfort level, preparedness to supervise others, and satisfaction with the initiative in the ambulatory curriculum. Results A total of 38 third-year residents were eligible to participate in the initiative, and 36 (94%) participated in the precepting session. Survey response rates were 76% and 78% for pre- and postsurveys, respectively. Resident survey scores of self-assessed teaching, precepting, and supervision skills increased from a mean of 25 out of 42 to 34 out of 42 (p < .001), with an average enjoyment score of 10.3 out of a possible 12, suggesting high learner satisfaction. Discussion The introduction of outpatient clinic precepting into the third-year internal medicine residency ambulatory curriculum was met with high participation and satisfaction and can be a successful approach to augmenting the outpatient residency experience.